APPLICATION OF SUGESTOPEDIA METHOD IN LEARNING WRITING - Teti Sobari; Dede Abdurrokhman (JLER (Journal of Language Education Research), 2018)
This study focuses on aspects of students' ability in writing through the use of suggestive methods. The formulation of the problem involves: Does suggestive method improve students' writing ability? and Effective suggestive suggestion method used in learning writing?The research method used is a descriftive method and research technique used is observation and test technique. The results showed that suggestive method is used in learning writing in class X SMK. This can be seen from students' responses to learning to be enthusiastic because students can write based on the structure and linguistic rules.The result of the analysis shows that the learning of writing by using suggestive method can be increased. It is shown at the time of pretest (before using) the method of suggestion the average score of students is 53,93. While the learning of writing by using the suggestive method on posttest has increased with the average value obtained by students 87.57. Thus the suggested method can improve students' writing skill of class X SMK.